2015
DOI: 10.1007/s00223-015-0099-x
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Role of Vitamin D on Neuromuscular Remodelling Following Exercise and Injury

Abstract: to systematically review the available evidence of the role of vitamin D on neuromuscular remodelling following exercise conditioning, exercise- or experimentally induced injury. We searched Medline (OVID platform), PubMed, Embase and Web of Science for randomised controlled trials (RCTs) including measures of neuromuscular function, injury and/or inflammation; a physiologically stressful intervention involving exercise conditioning, exercise- or experimentally induced injury and; vitamin D supplementation. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 39 publications
2
12
0
3
Order By: Relevance
“…Similarly to our results, studies in healthy subjects indicated that vitamin D intake did not improve muscle tropism and strength (Agergaard et al, 2015). The ability of the neuromuscular system to remodel in response to resistance rehabilitation training or following injury still remains to be understood (Minshull et al, 2016). Nevertheless, other Authors reported a high incidence of vitamin D deficiency in patients with ALS, and also found, at the 9-month follow-up, a slower decline in ALS-FRS-R scores in 20 patients treated with 2,000 IU of cholecalciferol per day compared with patients who did not take the same treatment (Karam et al, 2013).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similarly to our results, studies in healthy subjects indicated that vitamin D intake did not improve muscle tropism and strength (Agergaard et al, 2015). The ability of the neuromuscular system to remodel in response to resistance rehabilitation training or following injury still remains to be understood (Minshull et al, 2016). Nevertheless, other Authors reported a high incidence of vitamin D deficiency in patients with ALS, and also found, at the 9-month follow-up, a slower decline in ALS-FRS-R scores in 20 patients treated with 2,000 IU of cholecalciferol per day compared with patients who did not take the same treatment (Karam et al, 2013).…”
Section: Discussionsupporting
confidence: 72%
“…Moreover, vitamin D applied on motoneurons cultured in vitro seems to potentiate the effects of glial-and brainderived neurotrophic growth factors, protecting cells from Fas-induced cell death (Camu et al, 2014). Although ev- idence from the animal models suggests an effect of supplemental vitamin D on ALS, these positive results may not always extend to humans (Minshull et al, 2016;Blasco et al, 2015;Yang et al, 2016). Similarly to our results, studies in healthy subjects indicated that vitamin D intake did not improve muscle tropism and strength (Agergaard et al, 2015).…”
Section: Discussionsupporting
confidence: 48%
“…Vitamin D is positively associated with muscle function, muscle strength, and physical performance [6][7][8]. Furthermore, a meta-analysis of 13 RCTs reported a beneficial effect of vitamin D supplementation (800-100 IU/day) on measures of muscle strength and balance in individuals aged 60 years and older [9].…”
Section: Introductionmentioning
confidence: 99%
“…A metaanalysis of 30 RCTs in individuals of all ages showed a significant positive effect of vitamin D supplementation on muscle strength, which was most evident in people with a 25-hydroxyvitamin D 3 (25[OH]D 3 ) level < 30 nmol/L and in those who were older than 65 years [10]. Vitamin D plays a direct role on muscle quality via activation of the vitamin D receptors, which are involved in muscle protein synthesis and muscle growth [6,8]. Moreover, vitamin D is indirectly related to muscle function via the calcium-phosphate balance [6,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation